Morphology, flow cytometry and molecular assessment of ex-vitro grown micropropagated anthurium in comparison with seed germinated plants - Gantait, Saikat; Sinniah, Uma Rani (Academic Journals, 2011)
Micropropagated and seed propagated plantlets of anthurium (Anthurium andreanum Lind. cv. CanCan) were transferred to similar field condition and growth stage. A comparative study was conducted using morphological parameters, ploidy level assessment as well as deoxyribonucleic acid (DNA) fingerprinting using inter simple sequence repeat (ISSR) markers. The in vitro generated anthurium plants exhibited comparable vegetative growth and more sucker production when compared to plants propagated through seeds. No variation in ploidy level wasestablished through flow cytometric study. Genetic assessment through ISSR showed no polymorphism in banding pattern. It was revealed that there was no significant variation between micropropagated and seed propagated plants at ploidy and molecular level assuring the trueness of the micropropagated anthurium clones and their commercial applicability.